Home in A Hybrid World or To Dwell in A Networked Environment - Pot, Martin (Taylor & Francis, 2020)
Whilst our outside world is modifying into a more complex and hybrid networked world, our most intimate dwelling, our home, is at risk of falling behind as for many it seems to have remained the same as it has been for many decades. This book explores what it means to have a home in such a networked world. It describes what architecture can, or perhaps should, contribute to enable a more participatory role for inhabitants. This forward-thinking book will try to answer the question - What is the role and position of technology in our most intimate locations both now and what could it be like in the future?